The Spell of the Ancestors at the “Feast of Victory” (Nemlaay): From Initiation Ritual to Community Blessings - Antonio J. Guerreiro (Moussons)
In the month of June 2004, the village of Long Tuyo’—the first village above the rapids in the upper Mahakam area—decided to commemorate the anniversary of its foundation on the site (1904) by celebrating the Nemlaay Festival.The Festival, lasting six days, forms an initiation ritual for the young men and boys, besides a celebration of the warrior group proper. Now, the ceremony connected to headhunting and war until the 1950s, has taken new meanings. Although the core of the Nemlaay, i.e. the initiation rites and warrior training for the young boys and men—the live-saving force of the village during headhunting times—remain a martial value in society. Basically, Nemlaay rites emphasize status and inherited rank in connection to age and descent according to Long Glaat ideas. Since the last performance of the Nemlaay, other rituals and events have taken place in the area, such as the yearly Hudo’ Festival organized in turns by villages communities hosting the Festival, which is supported by the local tourism office, and the Dangé Great feast. During the last twenty years, I remark that the changes in the region have been tremendous. The article analyses the ritual processes and their underlying values in the frame of indigenous social and religious representations. Conversely, it gives a detailed account of Nemlaay ritual symbolism, in a comparative Indonesian perspective.